Recurrence of Fault Valve Behavior in a Continental Collision Area: Evidence From Tilt/Strain Measurements in Northern Adria - Rossi, Giuliana; Pastorutti, Alberto; Nagy, Ildiko; Braitenberg, Carla; Parolai, Stefano (Frontiers in Earth Science, 2021)
We analyzed the data recorded by the NE-Italy subsurface tilt and strainmeter network, evidencing a coherent transient signal in the recordings of four tiltmeter sites in the 1984-1990 period, producing a tilting along the main fractures. We used the uprise times to locate the transient signal source, borrowing from classical seismology techniques. The propagation velocity is compatible with a fluid diffusion process, starting from a source located close to the hypocenter of the February 10, 1983, Uccea earthquake, MD=4.2, at the estimated depth of 10.8 km. Our results add to the previous interpretation of a transient signal recorded by several GNSS stations in the 2006-2009 period in terms of fluid diffusion from below the Bovec basin. That source was located on the continuation to the NW of the Ravne fault, a few km to the NE from the present one, and about 6 km from the July 12, 2004, Bovec–Krn earthquake, Mw=5.1, depth 6.1 km. These observations suggest that the area is subject to fault-valve behavior episodes, releasing fluids trapped at depth to the surrounding region as pore-pressure bulges. The merging of Alpine and External Dinarides structures in this area puts highly permeable dolomitic limestones in contact with low-permeable fine-grained limestones and flysch formations. Therefore, the conditions for overpressure generation can be created, as evidenced by previous independent analyses in the study area for the 1983-1986 period. Fault movements, from time to time, in close relation with seismic events, can enable fluid diffusion in the surroundings. We also estimate the possible fluid influx needed to maintain the overpressure and the possible discharge across the faults. The paper provides insights on pore-fluid pressure variations related to slow slip events from a context different from subduction or transform margins, i.e., in a continental collisional area.